2022
DOI: 10.1164/rccm.202110-2274oc
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage–NLRP3 Activation Promotes Right Ventricle Failure in Pulmonary Arterial Hypertension

Abstract: Rationale: Pulmonary arterial hypertension (PAH) often results in death from right ventricular failure (RVF). NLRP3-macrophage activation may promote RVF in PAH. Objectives: Evaluating the contribution of the NLRP3 inflammasome in RV-macrophages to PAH-RVF. Methods: Rats with decompensated RV hypertrophy (RVH) [monocrotaline (MCT) and Sugen-5416 hypoxia (SuHx)] were compared with compensated RVH rats [pulmonary artery banding (PAB)]. Echocardiography and right heart catheterization were performed. Macrophages,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 48 publications
0
25
1
Order By: Relevance
“…A recent meta-transcriptome paper demonstrated that this transcript is a robust biomarker for human heart failure progression in the left ventricle ( Hua et al, 2020 ). Although Collagen alpha III is known to be regulated at both the mRNA ( Potus et al, 2018 ) and the protein ( Al-Qazazi et al, 2022 ) level in the male RV of MCT induced rats, we did not observe Col3a1 protein changes in our proteomic data. We do not have data to determine whether this reflects an experimental issue (such as inadequate sample size) or a statistical false discovery issue.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…A recent meta-transcriptome paper demonstrated that this transcript is a robust biomarker for human heart failure progression in the left ventricle ( Hua et al, 2020 ). Although Collagen alpha III is known to be regulated at both the mRNA ( Potus et al, 2018 ) and the protein ( Al-Qazazi et al, 2022 ) level in the male RV of MCT induced rats, we did not observe Col3a1 protein changes in our proteomic data. We do not have data to determine whether this reflects an experimental issue (such as inadequate sample size) or a statistical false discovery issue.…”
Section: Discussioncontrasting
confidence: 82%
“…These data in aggregate suggest that the MCT drug effect primarily impacts the RV rather than LV. Indeed, we have previously observed that the Nppa is expressed exclusively in the decompensated RV, but not the LV ( Al-Qazazi et al, 2022 ). We have reviewed the literature in an effort to identify compartment specific gene/protein expression, and reanalyzed the one available dataset where PAH was induced with MCT, and found that of the targets that map between platforms (microarray and RNAseq) ( Kittleson et al, 2005 ), none of our most robustly regulated RV genes were significantly regulated in that study of the LV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myeloid cell recruitment from bone marrow and blood has been highlighted as a key process in the development of vascular inflammation in PAH [140]. Furthermore, targeting right ventricular inflammation via the NLRP3 inflammasome has recently been described [141]. Correspondingly, circulating cytokine levels, including interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) are increased in PAH and correlate with mortality [142][143][144].…”
Section: Inflammation and Immune Activationmentioning
confidence: 99%
“…In this issue of the Journal , Al-Qazazi and colleagues (pp. 608–624 ) test the hypothesis that RV inflammation, driven by activation of the NLRP3 inflammasome in recruited macrophages, is a contributor to RV maladaptive remodeling in experimental pulmonary hypertension ( 9 ). The authors demonstrate that M1-polarized, monocyte-derived, CCR2 + macrophages are increased in RVs (but not LVs) of rats with monocrotaline- or sugen/hypoxia-induced pulmonary hypertension and highly express NLRP3.…”
mentioning
confidence: 99%